2020
DOI: 10.1016/j.joms.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Brachial Index Predicts for Difficulties in Performing Microvascular Anastomosis

Abstract: In reconstructive microsurgery, severe arteriosclerosis is a known predictor for free flap failure because of problems with the vascular anastomosis. We investigated whether the ankle brachial index (ABI) could be a suitable preoperative measurement for the prediction of compromise regarding vascular anastomosis in patients undergoing microsurgical reconstruction. Material and Methods: We conducted a prospective cohort study of patients who had undergone reconstructive microvascular surgery in a tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Further investigations found that pathologic ABI was related to difficulty with the microvascular anastomosis [80]. Furthermore, the wide variability concerning sensitivity and specificity of the ABI test must be considered [81].…”
Section: What Is the Prevalence Of Vascular Anomalies In The Present Sample?mentioning
confidence: 99%
“…Further investigations found that pathologic ABI was related to difficulty with the microvascular anastomosis [80]. Furthermore, the wide variability concerning sensitivity and specificity of the ABI test must be considered [81].…”
Section: What Is the Prevalence Of Vascular Anomalies In The Present Sample?mentioning
confidence: 99%
“…Повышение ЛПИ после реваскуляризирующих вмешательств у пациентов с КИ сопряжено с улучшением кровоснабжения оперированной нижней конечности и снижением клиники болевого синдрома [18]. Установлено, что предоперационное значение ЛПИ ассоциировано с состоянием сосудистой стенки и, как следствие, с тяжестью наложения сосудистого анастомоза [19]. В нашем исследовании отображено положительное прогностическое значение прироста ЛПИ у пациентов с ЗАНК, перенесших реваскуляризирующие операции [20].…”
Section: материал и методыunclassified